Bone Health of Apprentice Jockeys Using Peripheral Quantitative Computed Tomography - Greene, D. A.; Naughton, G. A.; Jander, C. B.; Cullen, S.-J. (International Journal of Sports Medicine, 2013)
Our aim was to use Peripheral Quantitative Computed Tomography (pQCT) to assess the bone health of male and female apprentice jockeys and age- and sex-matched peers. 2 groups of 25 young adults (n=50) (age range 15–38 years) were comprised of male and female apprentice jockeys, and male and female controls. We used pQCT to measure the distal tibia and distal radius. After covarying for weight and limb length, apprentice jockeys displayed less tibial cortical area and lower strength strain index at 14% distal shaft, 38% mid shaft and 66% proximal sites measured distally than controls (p=0.001). No between group differences were found in cortical density, trabecular area, and trabecular density at the tibia. Compared with controls, apprentice jockeys displayed greater trabecular density at the distal radial site (p=0.001), greater strength strain index at 66% proximal site measured distally (p=0.01), and a lower strength strain index at the distal radius (p=0.006). In conclusion, only trabecular density at the distal radius and strength strain index at the proximal radius were greater in apprentice jockeys than controls. Strategies to increase bone density and bone strength in apprentice jockeys should be considered by relevant industry stakeholders and their health providers.
Keywords: bone strength; jockey; musculoskeletal